2014
DOI: 10.1016/j.biopsych.2013.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Population-based Analysis of Alzheimer’s Disease Risk Alleles Implicates Genetic Interactions

Abstract: Background Reported odds ratios and population attributable fractions (PAF) for late-onset Alzheimer’s disease (LOAD) risk loci (BIN1, ABCA7, CR1, MS4A4E, CD2AP, PICALM, MS4A6A, CD33, and CLU) come from clinically ascertained samples. Little is known about the combined PAF for these LOAD risk alleles and the utility of these combined markers for case-control prediction. Here we evaluate these loci in a large population-based sample to estimate PAF and explore the effects of additive and non-additive interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 32 publications
1
54
1
Order By: Relevance
“…Another possibility is that the AD-associated sentinel SNPs which informed our analysis are AD specific and other pathologies such as vascular disease have stronger contributions to the cognitive decline in these cohorts. A recent study found evidence of synergistic interaction effects among ADassociated genes and the development of AD (Ebbert et al 2014). Thus, an association between AD risk genes and cognitive decline may involve more complicated relationships than have been tested here.…”
Section: Discussionmentioning
confidence: 78%
“…Another possibility is that the AD-associated sentinel SNPs which informed our analysis are AD specific and other pathologies such as vascular disease have stronger contributions to the cognitive decline in these cohorts. A recent study found evidence of synergistic interaction effects among ADassociated genes and the development of AD (Ebbert et al 2014). Thus, an association between AD risk genes and cognitive decline may involve more complicated relationships than have been tested here.…”
Section: Discussionmentioning
confidence: 78%
“…AD is characterized by the accumulation of amyloid plaques and neurofibrillary tangles in the brain. Many genetic loci exist that modify AD risk, but collectively, they explain only a fraction of AD’s heritability [2] and are not diagnostically useful [3,4]. Rare variants with large effects and epistatic interactions may account for much of the unexplained AD heritability, but are largely unknown due to limitations in traditional GWAS studies.…”
Section: Introductionmentioning
confidence: 99%
“…Rare variants with large effects and epistatic interactions may account for much of the unexplained AD heritability, but are largely unknown due to limitations in traditional GWAS studies. While rare variant and epistatic effects on AD are poorly understood, recent studies suggest that gene-gene interactions play a critical role in AD etiology and progression [3,57]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations